2021
DOI: 10.7717/peerj.11796
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the foliar phytochemical diversity of the avocado crop Persea americana cv. Hass in its susceptibility to pests and pathogens

Abstract: Phytochemical diversity (PD) can be considered as a defensive trait; it can operate through single plant secondary metabolites or usually as complex mixtures of them. We tested the more diversity-better defense hypothesis correlating the leaf plant secondary metabolites (PSMs) with the incidence of plant enemies on Hass avocado trees. We expected a negative correlation between the occurrence of plant enemies and PD metrics. Also, as intraspecific PSMs polymorphisms in plant populations are common, we studied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…It can also affect the diversity or structure of the community of herbivores feeding on host plants (Richards et al 2015, Volf et al 2018, Harrison et al 2018, Cosmo et al 2021, affect tri-trophic interactions (Wan et al 2017, Slinn et al 2018, and shape the diversity of the surrounding plant and microbe communities (Iason et al 2005, Zhang et al 2023. Other studies have instead found that intermediate or high levels of phytochemical diversity might be disadvantageous (Sternberg et al 2012, Pais et al 2018, found no/limited effects of it on herbivory (Torres-Gurrola et al 2011, Schuldt et al 2012, Espinosa-García et al 2021, or found no differences between different populations (Wolf et al 2012). On balance, results from these studies suggest that an increased phytochemical diversity is often, but not always, beneficial for plants.…”
Section: Phytochemical Diversitymeasures Of Combined Componentsmentioning
confidence: 99%
“…It can also affect the diversity or structure of the community of herbivores feeding on host plants (Richards et al 2015, Volf et al 2018, Harrison et al 2018, Cosmo et al 2021, affect tri-trophic interactions (Wan et al 2017, Slinn et al 2018, and shape the diversity of the surrounding plant and microbe communities (Iason et al 2005, Zhang et al 2023. Other studies have instead found that intermediate or high levels of phytochemical diversity might be disadvantageous (Sternberg et al 2012, Pais et al 2018, found no/limited effects of it on herbivory (Torres-Gurrola et al 2011, Schuldt et al 2012, Espinosa-García et al 2021, or found no differences between different populations (Wolf et al 2012). On balance, results from these studies suggest that an increased phytochemical diversity is often, but not always, beneficial for plants.…”
Section: Phytochemical Diversitymeasures Of Combined Componentsmentioning
confidence: 99%
“…Chemodiversity can change with domestication: for example, leaves of domesticated alfalfa show a higher saponin richness but a lower variability in saponin composition than the wild relatives (Robinson et al ., 2020). However, for domestication, plants with a high chemodiversity are becoming increasingly relevant, as they may be better protected against diseases (Espinosa‐García et al ., 2021). In conclusion, we need to simultaneously consider the mosaic of different niche realisation processes for a comprehensive understanding of eco‐evolutionary dynamics and ecosystem processes.…”
Section: Niche Realization Processesmentioning
confidence: 99%
“…The level of plant resistance to pests and pathogens has been related to the heterogeneity of the dynamic mosaic composition of structural, functional, and nutritional phytochemical diversity , Glassmire et al 2019. However, the homogeneity or heterogeneity in phytochemical diversity in terms of resistance will depend on the specific pest or pathogen (Espinosa-García et al 2021). For example, heterogeneity for a generalist consumer, such as Phytophthora cinnamomi, which can attack about 5,000 plant species belonging to more than 40 families (Hardham & Blackman 2018), will be different from that of a specialist such as the Abert's squirrel, which discriminates the chemotypes of pine trees of the same species when feeding on them (Snyder 1992).…”
Section: Gamma Phytochemical Diversity Pdγmentioning
confidence: 99%
“…Nevertheless, the random addition of plant secondary metabolites to a mixture does not assure its efficacy because antagonist interactions among the PSM may occur, and the plant consumers may detoxify that mixture (Whitehead et al 2021). Likewise, the sole addition of new phytochemical variants in a population does not imply increased stability or resistance against the local assemblage of consumers for the same reasons that may operate at the mixture scale (Espinosa-García et al 2021). Thus, the novel phytochemical combinations must undergo natural selection, leaving the combinations that add up to the plants' fitness or the population's persistence.…”
Section: Gamma Phytochemical Diversity Pdγmentioning
confidence: 99%